Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks. (15th March 2023) - Fan, Ye-Fei; Jiang, Hai-Long; Chen, Xiang-Feng; Li, Na; Wang, Xiao-Li; Lin, Jin-Ming; Zhao, Ru-Song
Graphical abstract: Highlights: A conjugated microporous polymers (TCB-CMPs) was synthesized at room temperature. TCB-CMPs is an ideal material for solid-phase extraction (SPE) of synthetic musks. The performance of the developed SPE column is better than most commercial columns. Green and effective method to quantify synthetic musks in food was established. Abstract: This study synthesized a conjugated microporous polymer (CMP) at room temperature, which has high surface area, large conjugate system, and nitrogen-rich features. The material was explored as a solid-phase extraction (SPE) column, and it showed a higher extraction efficiency for nitro-musks compared to most commercial columns. Under optimal SPE conditions, a sensitive and efficient method for determining five nitro-musks was established based on gas chromatography–mass spectrometry (GC–MS). The method showed excellent linearity (R 2  ≥ 0.996), low limits of detection (0.13–0.57 ng·L −1 ), good repeatability (1.1–4.0 %, n = 6) and was applied to the detection of trace nitro-musks in water and milk samples. The mechanism was further discussed combined with a simulation calculation. The advantages of the proposed method were mainly reflected in the extraction efficiency and sensitivity, which also indicated the potential of CMPs as a sample pretreatment material.